2018
DOI: 10.1186/s40694-018-0048-3
|View full text |Cite|
|
Sign up to set email alerts
|

Aspergillus niger is a superior expression host for the production of bioactive fungal cyclodepsipeptides

Abstract: BackgroundFungal cyclodepsipeptides (CDPs) are non-ribosomally synthesized peptides produced by a variety of filamentous fungi and are of interest to the pharmaceutical industry due to their anticancer, antimicrobial and anthelmintic bioactivities. However, both chemical synthesis and isolation of CDPs from their natural producers are limited due to high costs and comparatively low yields. These challenges might be overcome by heterologous expression of the respective CDP-synthesizing genes in a suitable funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 69 publications
0
32
0
Order By: Relevance
“…This finding proved that polycistronic secondary metabolite biosynthesis is possible in A. niger and suggested that the KivR enzyme catalyses the rate-limiting step in enniatin B biosynthesis [ 11 ]. It was furthermore demonstrated that A. niger is (i) a superior expression host not only for enniatin B, but also for beauvericin and bassianolide, by producing the highest titres ever reported for heterologous hosts as well as for natural producing organisms [ 12 ]; and (ii) an ideal platform strain for the production of new-to-nature CDPs obtained by designing and expressing hybrid CDP synthetases in A. niger [ 13 , 14 ]. Indeed, some of the novel CDPs displayed considerably higher bioactivities compared to their parental CDPs and reference drugs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding proved that polycistronic secondary metabolite biosynthesis is possible in A. niger and suggested that the KivR enzyme catalyses the rate-limiting step in enniatin B biosynthesis [ 11 ]. It was furthermore demonstrated that A. niger is (i) a superior expression host not only for enniatin B, but also for beauvericin and bassianolide, by producing the highest titres ever reported for heterologous hosts as well as for natural producing organisms [ 12 ]; and (ii) an ideal platform strain for the production of new-to-nature CDPs obtained by designing and expressing hybrid CDP synthetases in A. niger [ 13 , 14 ]. Indeed, some of the novel CDPs displayed considerably higher bioactivities compared to their parental CDPs and reference drugs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A. niger's metabolic diversity has been expanded to overproduce the secondary metabolites enniatin, bassianolide and beauvericin with high pharmaceutical application potential due to their antibacterial, antifungal and anticancer activities (Boecker et al 2018). Hence, A. niger is a powerful multipurpose cell factory producing a wide range of products, which-in such a diversity and efficiencyare not matched by any other fungal cell factory.…”
Section: Application Potentials Of Fungal Biotechnology: a Brief Surveymentioning
confidence: 99%
“…The esyn1 NRPS gene from Fusarium oxysporum was expressed in A. niger, leading to the production of enniatin at initial un-optimized titer of 1 mg.l -1 (Richter et al, 2014). Beauvericin and bassianolide were also heterologously produced after the cloning of the corresponding bbBeas and bbBsls synthetase genes from B. bassiana (Boecker et al, 2018). In these two studies, a promising A. niger heterologous expression host was developed based on the Tet-on bacterial-fungal hybrid expression system.…”
Section: Filamentous Fungi Heterologous Expression Systemsmentioning
confidence: 99%
“…The expression strength is directly correlated to the Dox concentration added, thus making Tet-on tuneable and very efficient, with expression levels equivalent to those obtained with the widely used strong constitutive promoter P gpdA (Meyer et al, 2011). In addition, the impact of the number of bbBeas gene copies integrated in A. niger genome on the beauvericin productivity was also investigated (Boecker et al, 2018). The strain harbouring a tandem gene copy produced approximately two-fold higher titers of beauvericin than the strain harbouring a single copy, under similar culture conditions (628 versus 294 mg•l -1 ).…”
Section: Filamentous Fungi Heterologous Expression Systemsmentioning
confidence: 99%